Integrating Character Education and Technology in Elementary Schools: A Qualitative Study of Curriculum Implementation - Danun Reyhan Ardiansyah; Moh. Fathurrahman (AL-ISHLAH: Jurnal Pendidikan, 2025)
Character education is a key component of Indonesia’s Merdeka Curriculum, which emphasizes the integration of Pancasila values into daily learning. However, effectively connecting character habituation with digital technology in elementary education remains a challenge.This qualitative case study was conducted at SD Negeri Sekaran 01 in Semarang, involving 26 participants: one principal, a curriculum coordinator, four subject teachers, and 20 fourth-grade students. Data were gathered through observations, semi-structured interviews, and documentation, and analyzed using Miles and Huberman’s interactive model.The study identified three main strategies for integrating character education with technology. First, routine habituation activities—including the 5S program (smile, greet, courtesy), morning prayers, literacy sessions, and singing national songs—reinforce discipline and nationalism. Second, project-based learning via the Pancasila Student Profile Projects cultivates collaboration, responsibility, and critical thinking. Third, ICT integration, starting in grade four, supports digital literacy, autonomy, and ethical technology use. Students responded positively to digital learning environments, finding them engaging and conducive to developing personal responsibility and curiosity.The integration of character education and ICT effectively supports the development of adaptive, religious, and disciplined learners aligned with 21st-century competencies. To sustain this hybrid model, teachers must design structured digital routines, curriculum developers should formally incorporate technology use, and policymakers need to ensure ongoing teacher training and ICT infrastructure.